ChemInform Abstract: Synthesis of 1, 5‐Diazaspiro[2.3]hexanes, a Novel Diazaspirocyclic System. Issue 34 (1st August 2013) - Zukauskaite, Asta; Mangelinckx, Sven; Callebaut, Gert; Wybon, Clarence; Sackus, Algirdas; De Kimpe, Norbert
Abstract The structurally new title compounds (VII) are synthesized from the easily accessible starting material (I) in eight steps.